Measurement of the W → ℓν and Z/γ* → ℓℓ production cross sections in proton-proton collisions at √s = 7 TeV with the ATLAS detector - Aad, Georges; Andrei, George Victor; Dietzsch, Thorsten; Hanke, Paul; Khomich, Andrei; Kluge, Eike-Erik; Kugel, Andreas; Männer, Reinhard; Meier, Karlheinz; Müller, Felix; Poddar, Sahill; Radescu, Voica; et al. (Journal of high energy physics, 2010)
First measurements of the W → ℓν and Z/γ*→ ℓℓ (ℓ = e, μ) production cross sections in proton-proton collisions at $ \sqrt {s} = 7\;{\text{TeV}} $are presented using data recorded by the ATLAS experiment at the LHC. The results are based on 2250 W → ℓν and 179 Z/γ* → ℓℓ candidate events selected from a data set corresponding to an integrated luminosity of approximately 320 nb. The measured total W and Z/γ∗-boson production cross sections times the respective leptonic branching ratios for the combined electron and muon channels are $ σ_W^{\text{tot}} $. BR(W → ℓν) = 9.96 ± 0.23(stat) ± 0.50(syst) ± 1.10(lumi) nb and $ σ_{{Z \left/ {γ } \right.}}^{\text{tot}} $BR(Z/γ∗ → ℓℓ) = 0.82 ± 0.06 (stat) ± 0.05 (syst) ± 0.09(lumi) nb (within the invariant mass window 66 < mℓℓ< 116GeV). The W/Z cross-section ratio is measured to be 11.7 ± 0.9(stat) ± 0.4(syst). In addition, measurements of the W+ and W− production cross sections and of the lepton charge asymmetry are reported. Theoretical predictions based on NNLO QCD calculations are found to agree with the measurements.
*The ATLAS Collaboration: G. Aad, V. Andrei, T.A. Dietzsch, P. Hanke, A. Khomich, E.-E. Kluge, A. Kugel, R. Maenner, K. Meier, F. Mueller, S. Poddar, V. Radescu, S. Schaetzel, V. Scharf, A. Schoening, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und sehr viele weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelzeichen
Gesehen am 31.10.2022